AVERAGE ALEX - no more. - Easther, Paul, 1954- (Conder, Australian Capital Territory : Paul Easther, 2023)
Annotation. In a world of extraordinary talents, meet Average Alex - a kid who faces everyday challenges, struggling with just being 'average'. He discovers that being 'average' is just the beginning. From awkward mishaps to failed attempts, Alex perseveres. But one day, an encounter unveils his unique ability, turning him into a star among his peers. 'Average Alex - no more' is an inspiring tale of finding your true potential, where every child learns that their moment to shine can come when they least expect it.
Keywords: Humorous fiction; Electronic books